AB0308 A Phase I Pharmacokinetic Study Comparing Pre-Filled Pen and Pre-Filled Syringe of SB5, An Adalimumab Biosimilar in Healthy Subjects. (15th July 2016) - Shin, D.; Lee, Y.; Kang, J.W.; Ellis-Pegler, R.
Abstract : Background: SB5 is developed as a biosimilar of the Adalimumab reference product (ADL). Equivalence in the pharmacokinetics (PK) between pre-filled syringe (PFS) of SB5 and PFS of ADL was demonstrated in a phase I study conducted in healthy subjects 1 and equivalent efficacy and comparable safety between PFS of SB5 and PFS of ADL up to week 24 were demonstrated in the phase III study conducted in patients with rheumatoid arthritis 2 . Objectives: To investigate and compare the PK, safety, and tolerability of the pre-filled pen (Pen) and PFS of SB5 in healthy subjects. Methods: This study was a randomised, open-label, single-dose, 2-arm, parallel group study in healthy subjects. Subjects were randomised in a 1:1 manner to receive a single 40 mg dose of SB5-Pen or SB5-PFS by subcutaneous injection on Day 1 and then were observed for 57 days during which the PK, safety, and tolerability measurement were made. The serum concentration of adalimumab was measured using an enzyme-linked immunosorbent assay. The primary PK parameters were area under the concentration-time curve from time zero to infinity (AUCinf ), area under the concentration-time curve from time zero to the last quantifiable concentration (AUClast ), and maximum concentration (Cmax ). Equivalence for the primary PK parameters was to be concluded if the 90% confidence intervals (CIs) for the ratio of geometric least squares means (LSMeans) of the groups compared were completely contained within the pre-defined equivalence margin of 0.8 to 1.25 using an analysis of variance. Results: Of 190 randomised subjects, 1 subject was excluded from the PK population in each arm (non-compliance with medication dosage in SB5-Pen and exclusion criteria met in SB5-PFS) and 188 subjects were analysed as PK population (n=94 in SB5-Pen and SB5-PFS each). Following single dose, the mean of AUCinf, AUClast, and Cmax were 2743.2 μg·h/mL, 2329.2 μg·h/mL, and 3.803 μg/mL for the SB5-Pen and 2503.3 μg·h/mL, 2182.2 μg·h/mL, and 3.673 μg/mL for the SB5-PFS. 90% CIs for the geometric LSMeans ratios of primary PK parameters for SB5-Pen and SB5-PFS were within the pre-defined equivalence margin of 0.8 to 1.25 (Table), confirming the bioequivalence between SB5-Pen and SB5-PFS. The proportion of subjects who experienced treatment-emergent adverse events (TEAEs) was comparable between the SB5-Pen and SB5-PFS (68.4% in SB5-Pen vs 60.6% in SB5-PFS). The most frequent TEAEs were upper respiratory tract infection (15.8% in SB5-Pen vs 19.1% in SB5-PFS). The majority of TEAEs were mild in severity. Only one subject in SB5-PFS experienced a moderate injection site reaction. Conclusions: This study demonstrated PK equivalence between SB5-Pen and SB5-PFS in healthy subjects. Both SB5-Pen and SB5-PFS were generally well tolerated with similar safety profiles. References: Shin D et al. Ann Rheum Dis. 2015; 74 (Suppl2: 459–460), FRI0110 Weinblatt ME et al. Arthritis Rheumatol. 2015; 67 (suppl 10), 8L Disclosure of Interest: D. Shin Employee of: Samsung Bioepis, Y. Lee Employee of: Samsung Bioepis, J. W. Kang Employee of: Samsung Bioepis, R. Ellis-Pegler Grant/research support from: Samsung Bioepis